2021
DOI: 10.3389/fmicb.2021.620798
|View full text |Cite
|
Sign up to set email alerts
|

Insect Derived Lauric Acid as Promising Alternative Strategy to Antibiotics in the Antimicrobial Resistance Scenario

Abstract: Antibiotic misuse is greatly contributing to an increase in antimicrobial resistance (AMR) in humans and animals. Natural and synthetic alternative strategies are being investigated in human and veterinary medicine, but little attention is paid to the antimicrobial effects of edible lipids, such as medium-chain fatty acids (MCFAs) and monoglycerides. Among MCFAs, lauric acid (LA) and its monoglyceride derivative, glycerol monolaurate (GML), exhibit the strongest antimicrobial activity. Coconut and palm kernel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 74 publications
0
50
0
Order By: Relevance
“…Lauric acid was reported as source of energy for fish feeding, resulting in a reduction in lipids in the liver [35]. Indeed, lauric acid is among the medium-chain fatty acids that can modulate intestinal health by regulating the level of IL-6 and TNF-α, and might contribute to appetite reduction [36]. Overall, irrespective of the type of diet, the concentration of total fatty acids in H. illucens larvae was dominated by saturated fatty acids (SFAs; 74%), followed by monounsaturated fatty acids (MUFA; up to 12%) and polyunsaturated fatty acids (PUFA; up to 14%).…”
Section: Hermetia Illucensmentioning
confidence: 99%
“…Lauric acid was reported as source of energy for fish feeding, resulting in a reduction in lipids in the liver [35]. Indeed, lauric acid is among the medium-chain fatty acids that can modulate intestinal health by regulating the level of IL-6 and TNF-α, and might contribute to appetite reduction [36]. Overall, irrespective of the type of diet, the concentration of total fatty acids in H. illucens larvae was dominated by saturated fatty acids (SFAs; 74%), followed by monounsaturated fatty acids (MUFA; up to 12%) and polyunsaturated fatty acids (PUFA; up to 14%).…”
Section: Hermetia Illucensmentioning
confidence: 99%
“…Besides, blending animal fats with vegetable oils may have synergistic effects, mainly arising from balanced ratios of saturated and unsaturated fatty acids [ 18 ]. Furthermore, MCFA, especially lauric acid, are ascribed a potentially favourable antimicrobial effect by disrupting the bacterial cell electron transport chain and consequently impairing the energy supply [ 12 , 19 , 20 ]. By influencing the microbial composition, effects of MCFA on the microbial fermentation profile can also result [ 21 ] and investigating microbial metabolites, such as biogenic amines and ammonia, as well as short-chain fatty acids (SCFA) that derive from protein or carbohydrate fermentation, could provide knowledge about the effects of HI larvae fat.…”
Section: Introductionmentioning
confidence: 99%
“…In poultry production, LA showed a strong ability to reduce the growth and colonization of pathogenic bacteria such as Campylobacter jejuni and Clostridium perfringens in chickens (7,8). Recently, it was reported that LA can be a promising alternative strategy to antibiotics in livestock nutrition (9). The possible mechanism is that LA has broad-spectrum antibacterial, antiviral and antifungal activities (10).…”
Section: Introductionmentioning
confidence: 99%
“…The possible mechanism is that LA has broad-spectrum antibacterial, antiviral and antifungal activities (10). It can penetrate bacterial cell membranes, destabilize their structures and cause cell lysis, and moreover, bacteria are unlikely to acquire resistance (9).…”
Section: Introductionmentioning
confidence: 99%